1994
DOI: 10.1200/jco.1994.12.3.553
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of low-dose continuous topotecan infusion in patients with cancer: an active and well-tolerated regimen.

Abstract: Twenty-one-day topotecan infusion is well tolerated at 0.53 mg/m2, with dose-intensity exceeding other schedules for administration of topotecan. The DLT is hematologic, with thrombocytopenia somewhat exceeding leukopenia. Objective responses were observed in seven patients with breast, ovarian, renal, and non-small-cell lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(49 citation statements)
references
References 5 publications
1
47
1
Order By: Relevance
“…In topotecan studies, the dose-limiting toxicity was also noncumulative myelosuppression, predominantly a severe neutropenia of brief duration not necessitating treatment delays (Rowinsky et al, 1992;Verweij et al, 1993). Thrombocytopenia and anaemia occurred mainly in regimens with prolonged intravenous topotecan administration (Hochster et al, 1994;Creemers et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In topotecan studies, the dose-limiting toxicity was also noncumulative myelosuppression, predominantly a severe neutropenia of brief duration not necessitating treatment delays (Rowinsky et al, 1992;Verweij et al, 1993). Thrombocytopenia and anaemia occurred mainly in regimens with prolonged intravenous topotecan administration (Hochster et al, 1994;Creemers et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In a phase I study with continuous intravenous topotecan administration for 21 days every 28 days in 44 patients with solid tumours, the MTD was 0.53 mg m-2 day-', with myelosuppression as DLT (Hochster et al, 1994). The steady-state lactone TPT concentration was low, approximately 4 ng ml-'.…”
Section: Prolonged Exposurementioning
confidence: 99%
“…No consistent relationship was found between drug level and haematological toxicity. Partial tumor responses were noted in two patients with ovarian cancer, one patient with breast cancer, one patient with renal cell cancer and one patient with non-small-cell lung cancer (NSCLC) (Hochster et al, 1994). Blood transfusions and platelet transfusions were necessary in 45% and 11% of patients respectively.…”
Section: Prolonged Exposurementioning
confidence: 99%
“…In the phase I study of heavily pretreated patients, the maximum tolerated dose was 0.53 mg m-2 day-' (Hochster et al, 1994). The starting dose of topotecan in the patients with advanced breast cancer was lower than that of the lung cancer patients because of previous exposure to marrow toxic treatments combined with the expected haematological toxicity of topotecan therapy.…”
Section: Treatmentmentioning
confidence: 99%
“…A phase I trial of low-dose continuous infusional topotecan in heavily pretreated patients reported objective responses with ovarian cancer, breast cancer and non-small-cell lung cancer. The dose-limiting toxicity was myelosuppression, with thrombocytopenia greater than neutropenia, seen at a dose level of 0.70 mg mi-2 day-' administered as a continuous 21-day infusion every 28 days (Hochster et al, 1994). Of 21 platinum-pretreated ovarian cancer patients receiving continuous 21-day infusional topotecan at a starting dose of 0.4 mg in-2 day-', nine patients responded (43%), including one complete responder (5%).…”
mentioning
confidence: 99%